How Many Water Molecules Does it Take to Dissociate HCl?. Issue 8 (15th January 2016) - Vargas‐Caamal, Alba; Cabellos, Jose Luis; Ortiz‐Chi, Filiberto; Rzepa, Henry S.; Restrepo, Albeiro; Merino, Gabriel
Abstract: The potential energy surfaces of the HCl(H2 O) n ( n is the number of water molecules) clusters are systematically explored using density functional theory and high‐level ab initio computations. On the basis of electronic energies, the number of water molecules needed for HCl dissociation is four as reported by some experimental groups. However, this number is five owing to the inclusion of entropic factors. Wiberg bond indices are calculated and analyzed, and the results provide a quadratic correlation and classification of clusters according to the nondissociated, partially dissociated, and fully dissociated character of the H−Cl bond. Our computations show that if temperature is not controlled during the experiment, the values obtained for the dipole moment (or for any measurable property) are susceptible to change, providing a different picture of the number of water molecules needed for HCl dissociation in a nanoscopic droplet. Abstract : Acid dissociation : High‐level ab initio and DFT computations show that four water molecules are needed for HCl dissociation, but this number increases to five if entropic factors are considered (see figure). The temperature affects the dipole moments obtained, giving a different picture of the number of water molecules needed for HCl dissociation in a nanoscopic droplet.